Role of the cardiologist in the management of oncology patients. Where are we standing, and what to expect in the future? - Paredes-Paucar, Cynthia (2021)
Cardiovascular and oncological diseases are the main causes of death worldwide. Cancer patients have an increased risk of cardiovascular diseases but, at the same time cardiovascular patients experience a higher risk of cancer. This relationship goes beyond the toxicity concerning cancer treatment. Cardio-oncology goal is to facilitate cancer therapy by implementing preventive strategies that allow early diagnosis and treatment of potential cancer therapy-induced cardiovascular complications, being heart failure the most fearest one. The creation of Cardio-oncology services has the potential to impact daily clinical practice and public health, with clear implications for the future.